Assessment of isokinetic muscle function in Korea male volleyball athletes - Kim, C. G.; Jeoung, B. J. (Journal of Exercise Rehabilitation, 2016)
Volleyball players performed numerous repetitions of spike actions, which uses and requires strong and explosive force, and control of the muscles of the shoulder, lower back, and legs. Muscle imbalance is one of the main causes of sport injuries. The purpose of this study was to assess isokinetic muscle functions in male volleyball players. We thus aim to accurately evaluate their muscle functions, and identify the best training strategy to achieve optimal muscle strength balance in future training programs. The participants in this study consisted of 14 male volleyball players. Muscle strength was measured using the isokinetic dynamometer. Muscle strength was evaluated in terms of peak torque and average power, calculated from five repeated measurements at an angular speed of 60°/sec. Three players who were left attackers showed shoulder imbalance, four players showed trunk joint imbalance, nine players had knee joint of extension/flexion imbalance and four players showed left/right imbalance. The results showed that the number of volleyball players with differences between the strength of the bilateral knee muscles, and between the strength of the hamstrings and quadriceps muscles was higher than the number of players with differences between the strength of the shoulder internal and external rotation muscles, and higher than the number of players with differences between the strength of the lower back extension and flexion muscles.